The Effect of Employee Training, Organizational Commitment and Self Efficacy on Employee Performance in the Hospitality Industry - Nurdjanah Hamid; Slamet Riyadi; Musran Munizu; Sitti Usmia; Helmi Ali (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study examined how self-efficacy, employee development, and organizational commitment affected workers' performance. The sample for this study, which incorporates quantitative research, consists of 70 permanent hotel employees. A saturated sampling approach is used in the sampling process. Techniques for gathering data include surveys, literature reviews, and supplementary secondary data. Validity tests, reliability tests, cross-tabulation tests, correlation tests, determination tests, simple linear regression, multiple linear regression, t-tests, and f-tests with SPSS 26.0 were all used in the data analysis process. The finding of this study demonstrates that organizational commitment, employee training, and self-efficacy are all factors that simultaneously affect employee performance. Employee performance is partially influenced by organizational commitment, employee training, and self-efficacy, but not by either factor alone. 0.647, or 64.7%, for the corrected R square. It is recommended for hotels to improve employee self-efficacy based on the magnitude (self-confidence) indicator. In addition to hotels having to increase employee training based on reaction indicators (participation in hotel activities) and behavior (becoming the best employee), hotels must also increase commitment based on affective indicators (paying attention).